UPDATE PERIOD OF EDUCATION SYSTEM - Sholdarov Dilshod Azimiddin O‘gʻli (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the continuity of the continuing education system, reforms in the education system, the level of coverage of the education system, the use of opportunities created for modern and world-class education. Proposals and recommendations on ways to increase competition in the education system on the basis of public-private partnership and to eliminate shortcomings in the education system and the education system are given.